Reasons to believe today - Martinetti, John, 1932- (Marquette studies in theology, 1996)
Christian faith is a keyhole through which one may glimpse the meaning of life and death. However this keyhole is not reliable if it is not supported by valid reasons to believe that God exists. This work examines belief systems and why people have turned their backs on God.